Strategies Model of Jember Historical Tourism Marketing - Kinanti, Lintang Anis Bena; Dr. Bambang Irawan, M.Si.,; Dr. Novi Puspitasari, S.E., M.M., (International Journal of Scientific Research and Management (IJSRM), 2020)
Jember has a long history since prehistoric times, and is evidenced by the diversity of relics from prehistoric times to the colonial period. Historical heritage objects become important regional assets that can generate profits and have a significant effect on economic development. One idea that can be initiated is the presence of an ancient museum. Because of that, an effective marketing strategy is needed to increase the people's visit to the museum and other historical tourism. This study aims to explore how the condition of ancient sites and objects in Jember, explore how the potential of building a museum as a location for storing ancient objects in Jember, and formulating marketing strategies on historical tourism and museums as part of Jember tourism programs. This research adheres to the positivist paradigm using qualitative research methods, using a case study approach by exploring the condition of ancient objects in the Jember area in detail. The results showed that the collection of ancient objects from Jember's history varied greatly with a total of more than 600. A number of collections have been placed in the Antiquities Collection Room, with very limited maintenance, and the room conditions that are not yet representative. For this reason, museum is an alternative solution as a place to store ancient art collection, as well as a part of historical tourism in Jember. The formulation of marketing strategy departs from the concept of SWOT Analysis which is then synergized with the concept of Tourism Marketing Mix.